Efficacy of music therapy on hospital induced anxiety and health related quality of life in Coronary Artery bypass graft patients: Study protocol for a randomized controlled trial. - ABEESHNA ASHOK,; AJITH SOMAN, (International Journal of Pharma and Bio Sciences, 2018)
Coronary artery bypass grafting (CABG) is a common surgery which enablesnew arteries to provide blood to the heart by makingthem bypass the obstructions in the patient’s coronary arteries. Anxiety is increased in CABG patients compared to any other surgeries as it is associated with the functioning of vital organs . Music therapy is one of the adjunct therapies which have an effect on patient’s anxiety. This study is to prove the effect of music therapy on hospital induced anxiety and health related quality of life in patients after CABG. In this assessor blinded randomized controlled trial (RCT) the efficacy of music therapy on post-operative anxiety and quality of life in CABG patients will be tested. The intervention group of 60 participants, aged between 30-80 years, will be selected to receive music therapy along with cardiac rehabilitation. The control group will receive cardiac rehabilitation alone twice a day. The primary outcome measures areHospital Anxiety and Depression score and secondary outcome measures are SF-36 and 6-minute walk distance. The primary outcomes will be measured by trained physiotherapist on preoperative day and post-operative days 2 & 7. Secondary outcomes will be measured on preoperative day and post-operative day 7. According to current knowledge this is the first outcome assessor blinded RCT on the efficacy of music therapy on hospital induced anxiety and health related quality of life in CABG patients and strictly follows consort guidelines (2010) with minimal confounding factors.